Pendampingan Metode Training dalam Peningkatan Soft Skill Public Speaking di SMK Al-Hadi Gresik - M. Fathor Rohman; Nur Ahid; Atsalitsa Fil Izzati (PT FORMOSA CENDEKIA GLOBAL, 2022)
In this mentoring-based research activity, we conducted public speaking training at SMK Al Hadi Gresik using the Asset Based Community Development (ABCD) method which aims to improve the quality of multimedia programs as a leading activity by optimizing students' soft skills so that they are better known by the wider community. Al-Hadi itself is a formal institution under the auspices of PPTQ Al-Hadi Ima'an Dukun Gresik, which has three activities for developing student potential, namely intracurricular, co-curricular, and extracurricular activities. The steps in this assistance are making workshops for the initial introduction of public speaking, training to become presenters and reporters, as well as practicing to become presenters and reporters. The result of this assistance is that it makes it easier for schools to find talents that exist in students in the field of presenting.